The effect of e-commerce livestreaming services on customer loyalty: A test of the chain mediation model - XinMei Ye; Hira Batool; Shi-Zheng Huang (Journal of Innovation and Entrepreneurship, 2023)
The outbreak of COVID-19 has made the offline real economy suffer an unprecedented test, and the online e-commerce livestreaming model, as a new marketing model, has been rapidly developed. Based on the SOR model, this paper clarifies the interaction between e-commerce livestreaming and consumer decision-making, taking the e-commerce livestream as an independent variable, customer engagement and value co-creation as intermediary variables, and customer loyalty as the dependent variable. This paper explores the evolution from e-commerce livestreaming to customer loyalty. The target sample consists of 475 Chinese e-commerce livestream viewers. Structural equation modelling (SEM) is used for empirical analysis, and MPLUS8.0 is used for data analysis. Aesthetic appeal, functional layout and verbal communication have a direct impact on customer engagement, while financial security, Nonverbal communication and service skills have no significant impact. In value co-creation, customer engagement has a direct impact on functional, hedonic and social values, which all have a direct impact on customer loyalty. Customer engagement does not singularly mediate between e-commerce livestreaming and customer loyalty, while value co-creation does have a mediating effect. Customer engagement and value co-creation have an enchained mediating effect between e-commerce livestreaming and customer loyalty. The research results reveal the effects of e-commerce livestreaming, provide a new entry point for considering stimuli in the application of SOR theory to e-commerce, and demonstrate how e-commerce livestreaming provides customers with visual beauty and personalized experiences while enhancing the communication skills of the operations and service staff. This research extends the scene theory of e-commerce livestreaming services and provides significant insights into e-commerce livestreaming platforms and enterprise management.
Keywords: 650; Value co-creation; Customer engagement; Customer loyalty; E-commerce live service scene; SOR model